PENGEMBANGAN MODUL PEMBELAJARAN PROGRAM LINEAR UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA - Gohae, Nelpi Kariana Wati (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2023)
The purpose of this research is to develop a linear programming module to improve understanding of mathematical concepts. The type of research carried out is research and development (R&D) with the ADDIE model, namely Analysis, Design, Development, Implementation, Evaluation. Data collection techniques are validation, questionnaires and tests. Data analysis techniques used are qualitative data and quantitative data. Based on the results of research and discussion, the linear programming module has met the valid, practical and effective criteria. The results of the validation of the material expert stage 1 with an average of 57.63% and categorized as less valid, the validation of the material expert stage II with an average of 88.89% and categorized as very valid and the validation of the material expert stage III with an average of 93.75% and categorized as very valid. Furthermore, the validation of media experts with an average of 76.62% and categorized as valid. Language expert validation with an average of 75% and categorized as valid. The average practicality result in the limited class trial was 4.21 with a percentage of 84.2% and was categorized as very practical. Furthermore, the field class trial with an average of 3.98 with a percentage of 79.6% and categorized as practical. The results of the effectiveness in the limited class trial obtained an average of 0.94 in the high category while for the field class trial the average was 0.80 with the high category. It is hoped that the Linear Program module developed can be used to gain understanding.